2019
DOI: 10.1136/bmjopen-2018-027495
|View full text |Cite
|
Sign up to set email alerts
|

Use of prescription opioids among patients with rheumatic diseases compared to patients with hypertension in the USA: a retrospective cohort study

Abstract: ObjectiveLong-term opioid prescribing has increased amid concerns over effectiveness and safety of its use. We examined long-term prescription opioid use among patients with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), psoriatic arthritis (PsA) and ankylosing spondylitis (AS), compared with patients with hypertension (HTN).MethodsWe used Truven MarketScan, a US commercial claims database (2003–2014) and identified RA, SLE, PsA and AS cohorts, each matched by age and sex to patients with HTN. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 46 publications
1
24
3
Order By: Relevance
“…This difference is likely driven by patients who were prescribed opioids to manage the pain associated with CIDs. Patients with CIDs are known to exhibit higher use of prescription opioids than the general population for pain management [40,41]. A study by Zhdanava et al that included patients with PsO reported rates of opioid use that were consistent with those of the present study (PsO cohort: 42.8%, matched non-PsO cohort: 30.7%) [41].…”
Section: Discussionsupporting
confidence: 85%
“…This difference is likely driven by patients who were prescribed opioids to manage the pain associated with CIDs. Patients with CIDs are known to exhibit higher use of prescription opioids than the general population for pain management [40,41]. A study by Zhdanava et al that included patients with PsO reported rates of opioid use that were consistent with those of the present study (PsO cohort: 42.8%, matched non-PsO cohort: 30.7%) [41].…”
Section: Discussionsupporting
confidence: 85%
“…One‐fifth of studies included only opioid‐naïve individuals (29 studies), mostly defined as the absence of opioid use in the 6 24,36,37,52,65,69–73 or 12 months 30,48,61,62,74–83 prior to the index date. Some studies investigated opioid use among patients with various specific health conditions: 43 studies 24,26–28,31,37,43,48,49,51,52,59,62,65,70,74,77–80,82–104 focused on noncancer pain, 14 studies 55,56,64,69,105–114 on musculoskeletal conditions, 13 studies 38–40,57,81,115–122 on injuries or trauma and eight studies 23,32,53,67,75,123–125 on infectious diseases. Seven studies 41,44,45,71,126–128 included patients with both cancer and noncancer pain, and six studies evaluated patients with cancer 60,129,130 or cancer survivors 61,131,132 .…”
Section: Resultsmentioning
confidence: 99%
“…Our study also has limitations. This initiative only addressed chronic noncancer‐associated pain, though such pain is the likely reason why patients with rheumatic diseases receive chronic opioid prescriptions (14). Also, although our EHR tracks the number of tablets per opioid prescription per month, it does not track the number of opioid prescriptions written per provider per month.…”
Section: Discussionmentioning
confidence: 99%